A Consensus Meeting on Expert Recommendations on Operating Specifications for Laparoscopic Radical Resection of Hilar Cholangiocarcinoma - Xiong, Yongfu; Jingdong, Li; Zhaohui, Tang; Lau, Joseph (Frontiers in Surgery, 2021)
Background With advances in techniques and technologies, laparoscopic radical resection of hilar cholangiocarcinoma (HCCA) has gradually been carried out in major medical centers in China. Its feasibility and safety have been accepted by a group of Chinese surgical experts. Methods To standardize perioperative management of HCCA using laparoscopic resectional approach, to ensure patient safety with standardized management, improve patient prognosis, and enable proper application and refinement of this surgical approach, the expert group on specifications for laparoscopic radical resection of HCCA in China organized a consensus meeting. Results Laparoscopic radical resection of HCCA is difficult and associated with high risks. Appropriate patients should be carefully selected, and this surgical approach should be promoted gradually. The Experts met and arrived at 16 recommendations on perioperative management of HCCA using laparoscopic surgery. There were 3 recommendations on preoperative diagnosis and evaluation, 1 recommendation on surgical principles of treatment, 1 recommendation on indications and contraindications, 1 recommendation on credentialing, staffing and equipments, 9 recommendations on laparoscopic techniques in different stages of operation and 1 recommendation on indications for conversion to open surgery. Conclusions Laparoscopic surgery for HCCA is still in the early phase of development. This consensus provides a clinical reference with the aim to promote and to facilitate its further developments.